Gitelman syndrome in a pediatric patient: a case report and literature review - Sun, Tianhong; Yang, Jing; Luo, Jiajia; Ma, Lina (Frontiers in Pediatrics, 2026)
ObjectiveThis article aimed to explore the clinical presentation, genetic underpinnings, and therapeutic approach to Gitelman syndrome (GS) in pediatric patients.MethodsThis article presents a detailed case report of a child with persistent hypokalemia, incorporating clinical evaluations, laboratory testing, treatment strategy, and whole-exome sequencing. A literature review was conducted to contextualize the findings.ResultsThe patient was found to carry compound heterozygous mutations in the SLC12A3 gene, with each inherited from a different parent. These mutations were identified as the primary cause of the child's refractory hypokalemia and impaired growth.ConclusionHypokalemia is a hallmark manifestation of pediatric GS. Genetic testing is instrumental for accurate diagnosis and differentiation from other hypokalemic conditions. The non-specific clinical phenotype of GS can lead to a missed or delayed diagnosis. In addition, co-occurrence of the p.T60M and p.T649M mutations is extremely rare in China. The presentation of this case underscores the need for heightened awareness of GS among pediatricians to enable early diagnosis and therapy, thereby optimizing the long-term quality of life of affected children.